Future-Anxious Commitment and Its Influence on Potential Human Capitals and Social Problems Anticipation With Personal Fides Awareness as Mediating Variabel - Muzalfitri Ridwan, Eka (Budapest International Research and Critics University, 2018)
South Sumatera is one of biggest city in Indonesia that has been developing in many kinds of infrastructures, not only in physical aspect but also in human resource aspect. One of trendsetter problems in that city are work status that are accustomed to having at professions like lecturers and teachers in South Sumatera generally and Palembang city specially. Many lecturers and teachers not only in state universities and state schools (like: elementary school, junior high school, and senior high school) but also in private universities and private schools have been having uncertain status that we can also say outsourcing lecturers and teachers since Indonesia Government decided a moratorium planning in recruiting candidates of public servants in Indonesia. It means, it will be big problems for lecturers and teachers in Indonesia (especially in South Sumatera), they will influence on public services (like: college students and students) even decrease potential human capital and other social problems because of lecturers’ and teachers’ uncertain status. Meanwhile in other countries (USA, England, Japan, New Zealand, Singapore, Germany, Korea, Philippine), outsourcing workers are a custom in those but it can not be implemented in South Sumatera because outsourcing workers in this city are not ready yet in their competencies, soft and hard skills, experiences, creative thoughts, internal motivations, independencies, and loyalty to the job. Besides that, there is custom in South Sumatera (Indonesia generally) that being an employee is a pride for themselves and their families even though the salaries are too low. This research had found two postulates to become novelties support motivation and commitment theoriesThe result of this research are there are strong influence of personal FIDES awareness on future-anxious commitment grades 0,98 (98%), strong influence of personal FIDES awareness on potential human capital grades 0,79 (79%), and strong influence of personal FIDES awareness on social problems anticipation grades 0,53 (53%). Personal FIDES awareness (PAFIDES) rises because of uncertain job status and job scarcity, and PAFIDES can not strongly and directly influence on social problems anticipation (SOCPRA) but it will be strongly if it indirectly influences on SOCPRA by using mediating variable called future-anxious commitment.